2017
DOI: 10.1038/s41467-017-01600-6
|View full text |Cite
|
Sign up to set email alerts
|

STIM1 promotes migration, phagosomal maturation and antigen cross-presentation in dendritic cells

Abstract: Antigen cross-presentation by dendritic cells (DC) stimulates cytotoxic T cell activation to promote immunity to intracellular pathogens, viruses and cancer. Phagocytosed antigens generate potent T cell responses, but the signalling and trafficking pathways regulating their cross-presentation are unclear. Here, we show that ablation of the store-operated-Ca2+-entry regulator STIM1 in mouse myeloid cells impairs cross-presentation and DC migration in vivo and in vitro. Stim1 ablation reduces Ca2+ signals, cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 66 publications
4
63
0
Order By: Relevance
“…All the ORAI and STIM isoforms are confirmed in DCs (16). As the major components of SOCC, Orai1 and STIM1 exhibit the most prominent impact on SOCE (17) and are critical for DC maturation (18)(19)(20). Nevertheless, there is a growing appreciation for the role of ORAI2 and STIM2 in the immune system.…”
mentioning
confidence: 99%
“…All the ORAI and STIM isoforms are confirmed in DCs (16). As the major components of SOCC, Orai1 and STIM1 exhibit the most prominent impact on SOCE (17) and are critical for DC maturation (18)(19)(20). Nevertheless, there is a growing appreciation for the role of ORAI2 and STIM2 in the immune system.…”
mentioning
confidence: 99%
“…After phagosome closure, periphagosomal Ca 2+ measured using quin‐2 was reported to be 50% greater than normal cytosolic levels . Recently, using the much more sensitive indicator Fluo‐8, Nunes and colleagues detected Ca 2+ hot spots around early phagosomes . This work and that of others has prompted speculation that phagosomal Ca 2+ release is important for downstream phagosome function, a topic that is discussed in detail below.…”
Section: Ca2+ Dynamics During Phagosome Maturationmentioning
confidence: 98%
“…Fluxes occurring as a result of or in close temporal association with receptor ligation during phagosome formation were discussed in Section 2 and summarized in Table . However, several studies inferred or observed additional, subsequent Ca 2+ release from early and late phagosomes . However, due to the difficulties in measuring phagosomal Ca 2+ concentration or release, there has been a paucity of data describing phagosomal Ca 2+ dynamics at various stages of maturation.…”
Section: Measurement Of Ca2+ Fluxes During Phagosome Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of ion flux has notably been fully appreciated following the molecular characterization of the store-operated Ca 2+ entry (SOCE) through Ca 2+ release-activated Ca 2+ (CRAC) channels mediated by the ORAI/STIM complex, best characterized in T cells. However, this system appears dispensable for key functions of macrophages and dendritic cells (DCs) while Ca 2+ signaling remains critical in these cells 2,3 . This observation points to the importance of alternative systems, yet to be discovered, that regulate the intracellular and luminal concentrations of Ca 2+ but also other ions including Na + , K + , Cl -, Mg 2+ or Zn 2+ for the control of immune responses.…”
Section: Introductionmentioning
confidence: 99%